The Effects of Subsidy Policy on Electric Vehicles and the Supporting Regulatory Policies: Evidence From Micro Data of Chinese Mobile Manufacturers - Liu, Xiang-Feng; Wang, Ling (Frontiers in Energy Research, 2021)
Subsidy policies are widely used in the electric vehicle industry in China. This study uses the perspective of the characteristics of subsidy policy and applies generalized propensity score matching (GPS) to estimate the impact of different subsidy policy intensities on the change in consumer demand for EVs and find the interval to optimize. The study shows that the optimization interval of the policy is in the 40%–70% treatment level, which maximizes the effect of the subsidy on China’s EVs. For a treatment effect lower than 40%, it is difficult to effectively create an incentive to enter the Es market in China because consumers think that the product is difficult to satisfy the demand of too low-end technology; by contrast, for the treatment level higher than 70%, the cost of the high endurance mileage power battery increases exponentially, and the complementary effect of subsidies is insufficient. Consequently, we propose three suggestions: The government should 1) use big data technology to supervise subsidies and design a real-time reporting mechanism and punishment mechanism for subsidy-misuse; 2) adopt the incentive regulation to promote the improvement of the endurance mileage of new energy vehicles (e.g., optimizing the subsidy ladder, innovating the form of subsidies) and gradually eliminate low-technology product; and 3) reasonably design a regulatory mechanism that increases the cost of fraud and breach of contract to encourage firms to truthfully report technical indicators.